Intrafamilial phenotypic variations in familial cases of cervical flexion induced myelopathy/Hirayama disease. Issue 1 (2nd January 2018) - Polavarapu, Kiran; Preethish-Kumar, Veeramani; Nashi, Saraswati; Vengalil, Seena; Prasad, Chandrajit; Bhattacharya, Kajari; Verma, Abha; Pruthi, Nupur; Bhat, Dhananjay I.; Nalini, Atchayaram
Abstract: Hirayama disease is generally considered to be a sporadic disorder, except for a few reports of familial occurrence. In this study, we describe eight patients from four families with cervical flexion induced myelopathy (CFIM)/Hirayama disease (HD) and intra-familial phenotypic variations. All underwent clinical and electrophysiological evaluation, while seven of them had contrast MR imaging of cervical spine in flexion. There was significant intra-familial variability: distal bimelic form in four patients, classical monomelic form in three and proximo-distal form in one. Irrespective of the clinical phenotype, MRI showed characteristic dynamic changes of posterior dural detachment with prominent epidural enhancement extending variably from C3 vertebral level to dorsal spine in six patients. One patient with 28 years of illness, had only lower cervical cord atrophy without dynamic changes while another patient demonstrated forward dural displacement with epidural enhancement even after 38 years of disease duration.